Venezuelan Refugees in Brazil: Communication Rights and Digital Inequalities During the Covid-19 Pandemic - Camargo, Julia (2022)
The article analyzes the experiences of Venezuelan refugees in the city of Boa Vista (Brazil) in exercising their communication rights in the context of social and digital inequalities aggravated by the Covid-19 pandemic. This article outlines a perspective on digital inequalities from a rights-based approach, which focuses on granting the right to communicate to those who lack it rather than providing access to technology without highlighting the structural changes that are needed for promoting representation and participation of marginalized communities. Building on online and face-to-face interviews with 12 Venezuelan refugees, we identified three scenarios where inequalities regarding access and uses of ICTs are materialized: (a) reduction of digital communication interactions and affective networks due to the deterioration of connectivity in Venezuela and the suspension of local communication services provided by humanitarian agencies; (b) barriers to accessing information about rights and basic services, such as education, health, work, and shelter, given the reduction of communication channels and the closure of reference centers supporting refugees; and (c) increased exposure to fake news, scams, and hate speech in social media platforms and message apps, generating disinformation and enhancing risks of exploitation and marginalization of refugees.